1997
DOI: 10.1097/00005392-199706000-00119
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factors in Bladder Wound Healing

Abstract: During the early phases of bladder wound healing (12-24 hours post injury), mRNA for KGF and TGF alpha increased, whereas TGF beta 2 and beta 3 and the KGFR and EGFR remain unchanged. Additionally, exogenous KGF has a direct effect on urothelial proliferation. KGF and TGF alpha warrant further study as potential mediators of bladder wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 0 publications
3
37
0
Order By: Relevance
“…Interestingly, no difference in the extent of UVB damage was seen in these mice in the absence of exogenous KGF. This finding is consistent with our result that -in contrast to many other situations where KGF expression is upregulated upon epithelial injury (Werner et al, 1992;Zeeh et al, 1996;Baskin et al, 1997;Charafeddine et al, 1999;Adamson and Bakowska, 1999) -enhanced KGF expression upon UV irradiation could be detected neither in murine skin nor in cultured fibroblasts (our unpublished data).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, no difference in the extent of UVB damage was seen in these mice in the absence of exogenous KGF. This finding is consistent with our result that -in contrast to many other situations where KGF expression is upregulated upon epithelial injury (Werner et al, 1992;Zeeh et al, 1996;Baskin et al, 1997;Charafeddine et al, 1999;Adamson and Bakowska, 1999) -enhanced KGF expression upon UV irradiation could be detected neither in murine skin nor in cultured fibroblasts (our unpublished data).…”
Section: Discussionsupporting
confidence: 93%
“…For instance, Chung et al reported a 3.2-4.5-fold increase in proliferation of limbal and peripheral cells after creation of a 3-mm wound in the cornea [18]. Baskin et al detected a six-to eightfold increase in transcription of keratinocyte growth factor and transforming growth factor alpha in full-thickness bladder tissue in vivo,12-24 h after the creation of surgical wounds in rat bladders [19], although actual changes in proliferation in response to wounding were not examined during this study. In both these cases, fully differentiated tissue was used and the wounds were significantly larger than the 500-800-m wounds considered here.…”
Section: Discussionmentioning
confidence: 99%
“…The FGFR2-IIIb signaling pathway can lead to mitogenesis, as is the case for basal cells of the skin or bladder wound healing, 35,36 and progression of tumors, as in poorly differentiated carcinomas of the stomach. 37,38 Alternatively, the same receptor may be implicated in the control of cell differentiation, as in the suprabasal cells of the skin 39 and in the maintenance of certain carcinomas in less aggressive forms as in this study and others.…”
Section: Tumorigenicity Of Fgfr2-iiib Re-expressing Hcc Cells In Vivomentioning
confidence: 99%